Human Resource Planning and Selection Strategy at PT Kimia Farma, tbk - Arifin, Antoni Ludfi (Majalah Ilmiah Bijak, 2022)
The objective of this study is to find out the strategy of planning and selection of human resources (HR) in PT Kimia Farma, Tbk. This study is qualitative research. This study's primary data were collected from interviews, observation, and recording, while secondary data were collected from the company and other external sources. Furthermore, the data were analyzed, and it is used to present the results of the study. The validity of the data is measured by evaluating the correctness of the data (triangulation). This study found that the company has implemented a human resource development strategy through 1) the planning programs for human resource requirements which support the organization's vision and mission; 2) the recruitment process is conducted openly with a rigorous selection process to determine and obtain qualified candidates based on requirements. This study also presents the results of the synthesis of HR planning & selection that can be used in the pharmaceutical industry and PT Kimia Farma, Tbk in particular.